(untitled) (Research, Society and Development, 2022)
The association between literature and psychology, specifically with psychoanalysis, is quite broad. Folktales, like fairy tales, present several themes that can be related to growth and psychological well-being. The aim of this article is to analyze, under the perspective of psychoanalysis, a Brazilian popular tale from European origin, collected by Silvio Romero and published in the volume called Contos Populares do Brasil (1954), which brings together Brazilian folk tales of European, Indian and African origin. The article focuses in a story collected in Rio de Janeiro, namely, A Mulher e a Filha bonita. In this sense, it was decided to use as theoretical framework the ideas proposed by Bettelheim (2003), Corso and Corso (2006) and Chevalier and Gueerbrant (2008), in order to perceive how images and concepts present in this popular tale reveal elements of the human psyche. The tale analyzed, namely, A Mulher e a Filha bonita, from the beginning present the maternal envy, and after that several themes from the female psyche are presented, among which the desire to become a wife and a mother are highlighted, desires that require maturation and important internal changes, which are visualized in the protagonist’s struggles throughout the construction of the narrative. What is evident from the analysis developed is a transformation of the girl into a woman, because the protagonist faces challenges, dilemmas and crises that result in a lot of transformations and the maturation of her personality throughout her journey.